Experimental Pain Responses in Children with Chronic Pain and in Healthy Children: How Do They Differ? - Jennie CI Tsao; Subhadra Evans; Laura C Seidman; Lonnie K Zeltzer (Pain Research and Management)
BACKGROUND: Extant research comparing laboratory pain responses of children with chronic pain with healthy controls is mixed, with some studies indicating lower pain responsivity for controls and others showing no differences. Few studies have included different pain modalities or assessment protocols.